2019
DOI: 10.1021/acsabm.9b00979
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electrical Stimulation Enhances Body Fluid Transport for Collagen Biomineralization

Abstract: Mechanical loads from physiologic activities such as walking and running generate bioelectricity in bones. By mimicking bioelectricity, external electrical stimulations have also been used therapeutically to stimulate bone-forming cells and, thus, to promote bone regeneration. However, little is known about the physicochemical mechanism(s) by which electrical stimulations drives calcium phosphate mineralization of collagen. Here, we showed that, during in vitro collagen mineralization in the absence of cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In addition, microbial metabolism induces formation and transformation of Fe-oxides, and these interactions contribute significantly to the global Fe cycle. , Biomineralization also occurs in the oceans on such a large scale that it influences many aspects of seawater chemistry and results in large-scale carbon sequestration in the form of carbonate sediments. Moreover, major classes of tissues, such as bones and teeth, are formed in animals and humans through biomineralization. ,,,,, …”
Section: Theme 3: Dissolution Nucleation and Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, microbial metabolism induces formation and transformation of Fe-oxides, and these interactions contribute significantly to the global Fe cycle. , Biomineralization also occurs in the oceans on such a large scale that it influences many aspects of seawater chemistry and results in large-scale carbon sequestration in the form of carbonate sediments. Moreover, major classes of tissues, such as bones and teeth, are formed in animals and humans through biomineralization. ,,,,, …”
Section: Theme 3: Dissolution Nucleation and Growthmentioning
confidence: 99%
“… Whether that matrix is insoluble and provides a scaffold for mineral formation or is soluble and acts to shape mineral products or drive dissolution, it manipulates energetic controls over ion transfer and phase transformation through processes that are inherently interfacial (Figure B,C). , Although few, if any, examples exist for which there is a clear understanding of the physicochemical mechanisms by which bioorganic matrices alter free energy landscapes and kinetic barriers to exert such controls, in vitro studies point towards a number of possibilities, ranging from the purely physical, such as the effects of confinement on mineral phase, shape, and orientation, , to chemically-defined processes, including the complexation of ions by highly charged macromolecules, stabilization of hydrated amorphous phases by both proteins and ions, and stereochemical effects that combine lattice matching with chemical reactivity to guide nucleation or modify crystal habits. In addition, living organisms can cause pulsed bioelectricity to trigger biomineralization, and repeated mechanical loading induced by their movements can also facilitate the transport of precursor molecules into confined spaces of organic matrices and direct biomineralization in specific locations with desired functionalities …”
Section: Theme 3: Dissolution Nucleation and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…4c). It has been shown that pulsed electrical signals can locally accelerate the nucleation of calcium phosphate nanocrystals in or on collagen and drive collagen calcium phosphate mineralization 36 . In addition, cells could mechano-sense matrix stiffness as they could apply contractile forces to fibrillar collagen, and there were reported that cells have durotaxis properties on stiffness gradients surface and migrate faster on harder surfaces 37 .…”
Section: μSpef Induced Ecm Remodeling To Promote Cell Migrationmentioning
confidence: 99%